Self-control with online shopping consumptive behavior’s relationship in higher education students - Lestari, Julita Lea; Timur, Hendryk; Safitri, Ellenia Eka (Interdisciplinary Social Studies, 2023)
This study aims to determine the relationship between self-control and online shopping consumptive behavior in students of the Faculty of Economics and Social Affairs at Jenderal Achmad Yani University Yogyakarta. The method used in this study is quantitative. The data collection method used is questionnaires or scales compiled by researchers, consisting of consumptive behavior and self-control scales. This research was conducted on 132 Faculty of Economics and Social Affairs students at Jenderal Achmad Yani University. The sample criteria in this study are aged 18-21 years where respondents are active students of the Class of 2020 of the Faculty of Economics and Social Affairs at Jenderal Achmad Yani University Yogyakarta and actively use online shopping platforms such as Shopee, Lazada, Bukalapak, Tokopedia, and others. The sampling technique used is purposive sampling, and the data analysis technique used is the Pearson Product Moment analysis technique.